(untitled) (International Journal of Engineering and Computer Science, 2018)
Software project managers are often faced with challenges when trying to effectively staff and schedule projects. Fail in scheduling correctly the execution of tasks leads to lower quality product to be delivered late and may over budget. An adequate model for software project planning has to deal with not only the problem of project task scheduling but also the problem of human resource allocation. The allocation of scarce resources then becomes a major objective of the problem. To develop a well-organized method for solving these issues, here an event based scheduler and an Ant Colony Optimization algorithm is used. The event based scheduler adjust the allocation of employees at events and keep the allocation unchanged at non-events. To solve the complicated planning problem, a well-organized Ant Colony Optimization algorithm is further designed. With the existing methods, resources and time are consumed by wasteful techniques such as student syndrome in which a person will only start to work on an assignment at the last possible moment of the deadline. It also delays the completion of task which is the impact of Parkinson’s law. For solving the issues related with the existing methods, critical chain project management techniques are used. Critical chain project management recommends that task estimates are cut to half the length of a normal duration. It also uses safety buffers to manage the impact of constraint variation and uncertainty around the project. Incorporating critical chain to the existing method yields an optimal plan.